Evaluación de manejo silvicultural y su influencia en la productividad en una plantación de Gmelina arborea Roxb. (Melina), establecida en la finca Santa Isabel, del cantón Valencia, provincia de los Ríos - Zambrano Requena , José Carlos (2023)
The species of Gmelina arborea, is of great economic importance in the country, therefore, it is of great interest in the development of research on this species to maintain the productivity and tree growth. The present investigation was carried out in the farm Santa Isabel, located in the Valencia country. The main objective of this study was given in the determination to evaluate the effects that occur in silvicultural management (thinning), in the productivity of a G. arborea plantation. Where rectangular plots of 20 x 50 m^2, (5 plots) to obtain dasometric data. The variables evaluated were DAP (m), commercial and total height (m), basal area m^2, commercial and total volume m^3, and finally, the mean annual increment (IMA).